Late Pleistocene to Holocene vegetation and climate changes in northwestern Chukotka (Far East Russia) deduced from lakes Ilirney and Rauchuagytgyn pollen records - Andreev, Andrei; Raschke, Elena; Biskaborn, Boris (Prof.); Vyse, Stuart Andrew; Courtin, Jérémy; Böhmer, Thomas; Stoof-Leichsenring, Kathleen R. (Dr.); Kruse, Stefan (Dr.); Pestryakova, Luidmila A. (Prof. Dr.); Herzschuh, Ulrike (Prof. Dr.) (Boreas, 2021)
This paper presents two new pollen records and quantitative climate reconstructions from northern Chukotka documenting environmental changes over the last 27.9 ka. Open tundra- and steppe-like habitats dominated between 27.9 and 18.7 cal. ka BP. Betula and Alnus shrubs might have grown in sheltered microhabitats but disappeared after 18.7 cal. ka BP. Although the climate was rather harsh, local herb-dominated communities supported herbivores as is evident by the presence of coprophilous spores in the sediments. The increase in Salix and Cyperaceae similar to 16.1 cal. ka BP suggests climate amelioration. Shrub Betula appeared similar to 15.9 cal. ka BP, and became dominant after similar to 15.52 cal. ka BP, whilst typical steppe communities drastically reduced. Very high presence of Botryococcus in the Lateglacial sediments reflects widespread shallow habitats, probably due to lake level increase. Shrub Alnus became common after similar to 13 cal. ka BP reflecting further climate amelioration. Simultaneously, herb communities gradually decreased in the vegetation reaching a minimum similar to 11.8 cal. ka BP. A gradual decrease of algae remains suggests a reduction of shallow-water habitats. Shrubby and graminoid tundra was dominant similar to 11.8-11.1 cal. ka BP, later Salix stands significantly decreased. The forest-tundra ecotone established in the Early Holocene, shortly after 11.1 cal. ka BP. Low contents of green algae in the Early Holocene sediments likely reflect deeper aquatic conditions. The most favourable climate conditions were between similar to 10.6 and 7 cal. ka BP. Vegetation became similar to the modern after similar to 7 cal. ka BP but Pinus pumila came to the Ilirney area at about 1.2 cal. ka BP. It is important to emphasize that the study area provided refugia for Betula and Alnus during MIS 2. It is also notable that our records do not reflect evidence of Younger Dryas cooling, which is inconsistent with some regional environmental records but in good accordance with some others.